PERFORMANCE ANALYSIS OF MICROTOMOGRAPHYSKYSCAN 1173 FOR LOW DENSITY MATERIALS - ODE SRI WAHYU (NIM: 20210001); Pembimbing 1:Dr.rer.nat. Freddy Haryanto ; Pembimbing 2:Dr.Siti N, WA
Performance evaluation in determining the image quality be a commonly thing to do since the micro-ct scan became a routine tools used in pre-clinical studies or small animal imaging studies. Microtomography system- SkyScan1173 is the high-energy type of micro ct that owned by BSC-ITB Laboratory. It has voltage < 130kV (Hamamatsu L9181-02) specifications with the capability for imaging materials with high density contrast. Therefore, a phantom was designed and fabricated mimics the density of human tissue with reference to the standards issued by the AAPM. Phantom used for evaluation the ability of micro-ct SkyScan 1173 in imaging materials which having a low density contrast. Performance evaluation of micro ct is done by changing the voltage, exposure, and camera resolutions parameters. Quantitative analysis is performed using ImageJ and CTAn software to determine the contrast scale, uniformity, SNR, and low contrast criteria/CNR. The results was obtained show that a voltage of 30 kV by changing the exposure at 0.155 mAs, 0.160 mAs, and 0.165 mAs, as well as the application of camera resolution 560x560 pixels and 1120x1120 pixels giving a significant values of contrast scale, uniformity, SNR, and low contrast criteria/CNR for imaging materials which have low density contrast.